Effects of treatment of hepatorenal syndrome before transplantation on posttransplantation outcome. A case-control study - ÖZDOĞAN, OSMAN CAVİT (My University, 2004)
Background: Pretransplant renal function is the major determinant of survival after liver transplantation (LTx). Patients with hepatorenal syndrome (HRS) have a poor outcome after LTx compared with patients transplanted without HRS.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Gastroenteroloji-(Hepatoloji); Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Gastroenterology and Hepatology; Health Sciences; GASTROENTEROLOJİ VE HEPATOLOJİ; Klinik Tıp; Klinik Tıp (MED); GASTROENTEROLOGY & HEPATOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Hepatoloji; Gastroenteroloji; Hepatology; Gastroenterology; hepatorenal syndrome; liver transplantation; posttransplantation; PRETRANSPLANT RENAL-FUNCTION; LIVER-TRANSPLANTATION; PROGNOSTIC VALUE; SURVIVAL; CIRRHOSIS; ALBUMIN; THERAPY; TERLIPRESSIN; TYPE-1; MODEL